Representasi Interaktif Foto Profil Jejaring Sosial Facebook - Syaifudin . (Rekam: Jurnal Fotografi, Televisi, Animasi)
This article discusses about the photos on famous social web in Indonesia and in the world, Facebook. The photo is used as a profile photo. The images of photos are analyzed using the theory of social semiotics that proposed by Gunther Kress and Theo Van Leeuwen. With his theory of interactive representation of the photographs can be analyzed through the elements of gaze, framing and perspective so that a profile picture will be able to give the meanings of social interaction and relation of participant.Respond, personal distance-social distance, and involvement of participant of social web can occur when there is visual interaction through the profile photo or picture.